2013
DOI: 10.3109/00498254.2013.831143
|View full text |Cite
|
Sign up to set email alerts
|

Trametinib, a first-in-class oral MEK inhibitor mass balance study with limited enrollment of two male subjects with advanced cancers

Abstract: 1. This study assessed the mass balance, metabolism and disposition of [(14)C]trametinib, a first-in-class mitogen-activated extracellular signal-related kinase (MEK) inhibitor, as an open-label, single solution dose (2 mg, 2.9 MBq [79 µCi]) in two male subjects with advanced cancer. 2. Trametinib absorption was rapid. Excretion was primarily via feces (∼81% of excreted dose); minor route was urinary (∼19% of excreted dose). The primary metabolic elimination route was deacetylation alone or in combination with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 25 publications
3
20
0
Order By: Relevance
“…Symbols denote male (triangles) and female (circles) subjects followed by a protracted elimination phase likely reflective of slow elimination from deep compartments. It has been shown that parent trametinib, but not metabolites, preferentially distributes to red blood cells and this accounts for the initial rapid distribution phase [22] and is supportive of the observation that following a single i.v. dose, parent trametinib accounts for 52% (range 43%-63%) of the total radioactivity in plasma.…”
Section: Figuresupporting
confidence: 67%
“…Symbols denote male (triangles) and female (circles) subjects followed by a protracted elimination phase likely reflective of slow elimination from deep compartments. It has been shown that parent trametinib, but not metabolites, preferentially distributes to red blood cells and this accounts for the initial rapid distribution phase [22] and is supportive of the observation that following a single i.v. dose, parent trametinib accounts for 52% (range 43%-63%) of the total radioactivity in plasma.…”
Section: Figuresupporting
confidence: 67%
“…1). Information on the SOMs of the KIs metabolized by human CYP3A4 was obtained from the published literature and from product information (Glivec, 2001;Iressa, 2003;McKillop et al, 2004;Gschwind et al, 2005;Ling et al, 2006;Nexavar, 2006;Sutent, 2006;Tarceva, 2006;Sprycel, 2007;Tykerb, 2007;Christopher et al, 2008b;Minami et al, 2008;Tasigna, 2008;Shilling et al, 2010;Votrient, 2010;Castellino et al, 2012;Speed et al, 2012;Zelboraf, 2012;Caprelsa, 2013;Deng et al, 2013;Jakavi, 2013;Stivarga, 2013;Tafinlar, 2013;Xalkori, 2013;Bosulif, 2014;Ding, 2014;Dowty et al, 2014;Ho et al, 2014;Iclusig, 2014;Mekinist, 2014;Smith et al, 2014;Goldinger et al, 2015;Imbruvica, 2015;Johnson et al, 2015;Lacy et al, 2015;Loi et al, 2015;Scheers et al, 2015;Xeljanz, 2015;Zydelig, 2015;Abbas and Hsyu, 2016;Cotellic, 2016;Dickinson et al, 2016;Dubbelman et al, 2016;Lenvima, 2016;…”
Section: Methodsmentioning
confidence: 99%
“…In two patients given a dose of 2 mg of [(14)C]trametinib, 81% was detected in the feces and 19% was found in the urine. Trametinib is primarily metabolized via deacetylation [15].…”
Section: Pharmacokinetics and Metabolismmentioning
confidence: 99%